11C-PBR28 imaging in multiple sclerosis patients and healthy controls: test-retest reproducibility and focal visualization of active white matter areas - Park, Eunkyung; Gallezot, Jean-Dominique; Delgadillo, Aracely; Liu, Shuang; Planeta, Beata; Lin, Shu-Fei; O’Connor, Kevin C.; Lim, Keunpoong; Lee, Jae-Yun; Chastre, Anne; Chen, Ming-Kai; Seneca, Nicholas; et al. (European journal of nuclear medicine and molecular imaging, 2015)
Purpose Activated microglia play a key role in inflammatory demyelinating injury in multiple sclerosis (MS). Microglial activation can be measured in vivo using a positron emission tomography (PET) ligand 11 C-PBR28. We evaluated the test-retest variability (TRV) and lesion detectability of 11 C-PBR28 binding in MS subjects and healthy controls (HCs) with high-resolution PET. Methods Four clinically and radiologically stable relapsing-remitting MS subjects (age 41 ± 7 years, two men/two women) and four HCs (age 42 ± 8 years, 2 two men/two women), matched for translocator protein genotype [two high- and two medium-affinity binders according to DNA polymorphism (rs6971) in each group], were studied for TRV. Another MS subject (age 41 years, male) with clinical and radiological activity was studied for lesion detectability. Dynamic data were acquired over 120 min after injection of 634 ± 101 MBq 11 C-PBR28. For the TRV study, subjects were scanned twice, on average 1.4 weeks apart. Volume of distribution ( V T ) derived from multilinear analysis (MA1) modeling ( t * = 30 min, using arterial input data) was the main outcome measure. Results Mean test V T values (ml cm −3 ) were 3.9 ± 1.4 in the whole brain gray matter (GM), 3.6 ± 1.2 in the whole brain white matter (WM) or normal-appearing white matter (NAWM), and 3.3 ± 0.6 in MS WM lesions; mean retest V T values were 3.7 ± 1.0 in GM, 3.3 ± 0.9 in WM/NAWM, and 3.3 ± 0.7 in MS lesions. Test-retest results showed a mean absolute TRV ranging from 7 to 9 % across GM, WM/NAWM, and MS lesions. High-affinity binders demonstrated 30 % higher V T than medium-affinity binders in GM. Focal 11 C-PBR28 uptake was detected in two enhancing lesions of the active MS patient. Conclusion High-resolution 11 C-PBR28 PET can visualize focal areas where microglial activation is known to be present and has good test-retest reproducibility in the human brain. 11 C-PBR28 PET is likely to be valuable for monitoring both MS disease evolution and response to therapeutic strategies that target microglial activation.